In Concert with the Ecosystem - Edward P. Bass (Symphony in the Flint Hills, 2010)
I first “discovered” the Flint Hills of Kansas in the mid-1980s after working for a period of ten years to develop sustainable rangeland practices for a challenging grassland system located in the dry tropics of northwestern Australia.
Keywords: grassland; prairie; fire; ecosystem; eco; conservation; wild; nature; native; rancher; ranch; ranching; cattle; grazing; farming; cowboy; tradition; elements; plants; grasses; animals; harvest; forage; biodiversity; climate; bluestem; Indian; switch grass; burn; pasture